PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN DENGAN BENEISH M-SCORE PADA PERUSAHAAN L-Q 45 - Agnes Yuriko Elestine; Pardhita Tyas Palupi (Prosiding Seminar Nasional Pakar, 2019)
This study aims to analyze the effect of fraud triangle that is proxied bypressure, opportunity, and rationalization to influence fraud that occurs in thecompany's financial statements. The research method was carried out by usingquantitative research with 40 samples taken in the LQ45 in the period 2015-2017. The type of data used is secondary data. Analysis of the data used is theBeneish Ratio Index, which is then included in a model, the Beneish M-ScoreModel using five calculated Days Days in Receivable Index (DSRI), Gross marginIndex (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI),Depreciation Index (DEPI). The results of this study indicate that based on theBeneish M-Score, that ROA has no significant effect on FFR. AGROW has aneffect on FFR. LEV has no significant effect on FFR.